Polarization Labelling Spectroscopy for NaLi - Dung, Nguyen Tien; Khoa, Dinh Xuan; Bang, Nguyen Huy; Trong, Pham Van (Communications in Physics, 2011)
We use the polarization labelling spectroscopy technique for simplification of the spectra of alkali-metal NaLi molecule. As a result, the rotational resolution observation for NaLi in the 21 electronic state is reported for the first time.